A new genus of Podoscirtini with one new species from Guangxi, China (Orthoptera: Gryllidae; Podoscirtinae) - Zhixin, He; Tao, Zhang; Weiliang, Xie; Li, Lin; Libin, Ma (Zootaxa, 2021)
A new species, Pluviam guangxiensis is described from Guangxi Province, China. It is distinct from the known genera and species of Podoscirtinae. Details are provided. Thus, a new genus, with one new species, was established. Supplementary information relating to Xuanwua motuoensis He, 2015, which is very similar is provided.